Potention of Active Charcoal from Musa Paradisiaca and Manihot Utilissima Shell in Degrading River Contamination - Nurlailah Nurlailah; Anny Thuraidah; Yayuk Kustiningsih (Medical Laboratory Technology Journal, 2018)
River water is one of type water surface which is a lot of finding in South Kalimantan. Generally, this water used by the citizen for cooking and bathing. But along with era growth, this river becomes as disposal of various industrial waste. The contamination of heavy metal like Fe, Mn, Pb, Cd, and turbidity enhance progressively and degrade the water quality. Some natural substance which can be used to improve river water quality is active charcoal from Musa paradisiaca and Manihot utilissima shell which is easy to get. Target research is determined to find optimum dose of active charcoal from Musa paradisiaca and Manihot utilissima shell that capable to degrade heavy metal contamination and turbidity in water river. It used experimentally with pretest and post-test with control group design. A result of research showed the optimum dose of active charcoal Musa paradisiaca shell was 15 gram , it could absorb Pb 28,8% and Mn 24,6%, but 10 gram can degrade turbidity until 83,8 %, while the optimum dose of Manihot utilissima shell to 25,4% Pb and degraded 77,5% of turbidity was 15 gram. Statistical test result with Kruskal Wallis got the p-value less than 0,05 it meant there was a difference between the treatment of active charcoal from Musa paradisiaca and Manihot utilissima shell in degrading the contamination. A conclusion is those active charcoal having a potential to enhance the water river quality. Suggested to use another activator to the potential like stirring, time of contact and the different mass.